Domestic grid-friendly appliance controller with demand response for underfrequency load shaving - Muawiya, Abubakar Kaigama (2016)
The smart grid has modified and upgraded the existing traditional grid, these modifications solve lots of shortcomings of the existing traditional grid in terms of energy generation and utilization, it also provides a platform for researchers to ponder on. Among the modifications include adaptive and computational intelligence, improved automation, clean energy integration, 2-way communication and energy flow, improved security, reliability, and end-user conveniences. The traditional grid approach of restoring stability when all measures are exhausted is the conventional load shedding way. However, this type of load shedding subject end-users connected to the affected bus to experience a blackout and absolute discomfort. The smart grid in its early quest to optimize load shedding proffer adaptive and computational schemes which still performs below par. Demand Side Load Management (DSLM) provides a better means of mitigating load shedding than the latter, it also minimizes CO2 emission contributed by fossil fuel turbines and maximizes energy utilization. Domestic Grid-Friendly Appliance Controller (DG-FAC) is one of the contenders in DSLM, it provides support to grid stability and overcomes the bottleneck of 2-way communication in smart grid realization. DG-FAC manage Grid Friendly Appliance (GFA) loads autonomously based on frequency stability levels of the single-phase voltage, it also automates home surrounding security lightings control to optimum operational hours. The research work conducted involves design and hardware implementation of DG-FAC; this encompasses User Demand Response (UDR), frequency stability sensor and illuminance sensor as the input unit to the system and built on MXP connector “A” of myRIO-1900 module whereas embedded coding utilizing Field Programmable Gate Array (FPGA) personality of myRIO in LabVIEW was developed as the processing unit, and a driver circuit to Solid State Relays (SSR) was built on MXP connector “B”. The SSR controls the flow of supply to GFA loads by sending digitals signal which depends on frequency level and UDR. The design was simulated in LabVIEW and Multisim and then implemented on a hardware platform. The test result signifies that the implementation DG-FAC hardware is feasible. DG-FAC shaves two HVAC loads in the Stage-I and three in Stage-II but cannot support any further after these stages. The simulation of aggregated DG-FAC of one hundred smart homes connected to the same bus indicates that DG-FACs can act as spin reserve (SR), and may provide flexible SR of 24.35% to 42.19% of active loadings between Stage-I and Stage-II respectively, this will avert any conventional load shedding that may require shedding of active loading between 24.35% to 42.19% in similar scenario with little or no inconveniences by virtue flexible UDR freedom, and hence improves system security. The implementation of DG-FAC showcase a new paradigm of detecting frequency instability via LabVIEW real-time, adds to the number of few existing GFA controller hardware, improves GFA utilization with daily activities of lighting automation, and provide a platform for a flexible open-ended design utilizing FPGA and LabVIEW capabilities which include parallelism of executing task.Stage-I and Stage-II respectively, this will avert any conventional load shedding that may require shedding of active loading between 24.35% to 42.19% in similar scenario with little or no inconveniences by virtue flexible UDR freedom, and hence improves system security. The implementation of DG-FAC showcase a new paradigm of detecting frequency instability via LabVIEW real-time, adds to the number of few existing GFA controller hardware, improves GFA utilization with daily activities of lighting automation, and provide a platform for a flexible open-ended design utilizing FPGA and LabVIEW capabilities which include parallelism of executing task